The Immature Fiber Mutant Phenotype of Cotton (Gossypium hirsutum) Is Linked to a 22-bp Frame-Shift Deletion in a Mitochondria Targeted Pentatricopeptide Repeat Gene. Issue 6 (1st June 2016) - Thyssen, Gregory N; Fang, David D; Zeng, Linghe; Song, Xianliang; Delhom, Christopher D; Condon, Tracy L; Li, Ping; Kim, Hee Jin
Abstract: Cotton seed trichomes are the most important source of natural fibers globally. The major fiber thickness properties influence the price of the raw material, and the quality of the finished product. The recessive immature fiber ( im ) gene reduces the degree of fiber cell wall thickening by a process that was previously shown to involve mitochondrial function in allotetraploid Gossypium hirsutum . Here, we present the fine genetic mapping of the im locus, gene expression analysis of annotated proteins near the locus, and association analysis of the linked markers. Mapping-by-sequencing identified a 22-bp deletion in a pentatricopeptide repeat (PPR) gene that is completely linked to the immature fiber phenotype in 2837 F2 plants, and is absent from all 163 cultivated varieties tested, although other closely linked marker polymorphisms are prevalent in the diversity panel. This frame-shift mutation results in a transcript with two long open reading frames: one containing the N-terminal transit peptide that targets mitochondria, the other containing only the RNA-binding PPR domains, suggesting that a functional PPR protein cannot be targeted to mitochondria in the im mutant. Taken together, these results suggest that PPR gene Gh_A03G0489 is involved in the cotton fiber wall thickening process, and is a promising candidate gene at the im locus. Our findings expand our understanding of the molecular mechanisms that modulate cotton fiber fineness and maturity, and may facilitate the development of cotton varieties with superior fiber attributes.